Kepastian Hukum bagi Foregin Direct Investment (FDI) dalam Skema Kerjasama Pemerintah dengan Badan Usaha (KPBU) di Ibu Kota Nusantara (IKN) - Khalisha Erfira Septianita (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
The arrival of foreign investors in the development of the IKN must be followed by legal protection for foreign investors because it is very important to attract and retain investors who come. Legal protection provided to foreign investors consists of guarantees of legal certainty, guarantees of protection for foreign investors against non-commercial risks, guarantees of equal treatment for all investors and guarantees against nationalization and other takeover actions. The purpose of this study is to provide legal certainty for Foreign Direct Investment (FDI) in the government cooperation scheme with KPBU in the IKN. In conducting this research, the author uses a normative legal research method and is descriptive analytical in nature. The legal sources that form the basis of the KPBU scheme are regulated in Law No. 25 of 2007 concerning Investment, and Presidential Regulation No. 38 of 2015 which regulates KPBU in the provision of infrastructure. In addition, the government also provides support in the form of guarantees for investors, which aims to minimize the risks faced by the Implementing Business Entity (BUP) in infrastructure projects in the IKN. Projects such as Palapa Ring and SPAM Umbulan are real examples of the success of the KPBU scheme in the context of national infrastructure.